OZN in boj proti mednarodnemu terorizmu - Prezelj, Iztok (Teorija in praksa, 2016)
The United Nations (UN) dealt with the threat of international terrorism in a very limited sense during the Cold War. After 9/11, when terrorism was perceived as a threat to international peace and security, it forged a more comprehensive approach. This article shows the growing role of the UN in the fight against international terrorism and explores the comprehensiveness of its approach. The paper is based on the argument that the state of global counterterrorism has significantly improved due to the comprehensive and systematic approach of the UN; however, several system-level challenges remain. The paper specifically focuses on the challenges of the effectiveness of counterterrorism measures and the simultaneous need to respect human rights, the problem of the expanded role of the Security Council as a permanent legislator in counterterrorism, the problem of implementing the measures adopted, and the problem of coordinating a broad spectrum of counterterrorism measures.
Keywords: boj proti terorizmu; Človekove pravice; Human rights; International organizations; International security; International terrorism; Mednarodna varnost; Mednarodne organizacije; Mednarodni terorizem; OZN